The ethics of financial market making and its implications for high-frequency trading - Roncella, Andrea (Journal of business ethics, 2022)
During the last 20 years, the financial sector has undergone an unprecedented transformation due to new regulations and the implementation of several technological advancements. The combination of regulation and technology has brought about new financial processes that have fundamentally changed how financial market making is done. This paper studies the ethics of financial market making and its implications for one of the most controversial financial innovations of modern times, namely high-frequency trading (HFT). We claim that the Aristotelian distinction between natural chrematistics, which is aimed at serving the real economy, and unnatural chrematistics, whose ultimate purpose is wealth accumulation, can be a useful criterion to assess the ethics of financial market making and the goodness of an innovation as HFT, and how it can serve the common good of society. This approach can be defined as ‘purpose oriented’ or ‘purpose fulfillment’.